Green Synthesis of Silver Nanoparticles and Their Anticancer Potential: A Review (International Journal of Food and Nutritional Sciences, 2022)
This review explores the synthesis of silver nanoparticles using green chemistry methods and examines their potential applications in cancer treatment. Green synthesis methods are gaining popularity due to their eco-friendly approach, utilizing natural sources like plant extracts or microorganisms to reduce silver ions into nanoparticles. The review discusses the various synthesis techniques, their advantages, and the mechanisms through which silver nanoparticles exhibit anticancer properties. Furthermore, it analyzes recent research findings on the effectiveness of these nanoparticles against different types of cancer cells, highlighting their promising role in future cancer therapies.